Сучасні методи підвищення ефективності роботи акумуляторів - Євдокименко, В. Я. (ХНУРЕ, 2025)
In today’s world, smartphones play a central role in everyday life, relying heavily on the efficiency and reliability of their batteries. Lithium-ion and lithium polymer batteries are widely used due to their high energy density and compact size. However, overheating remains a significant issue, affecting both the battery life and the safety of the device. The heating process is influenced by internal resistance, exothermic reactions, and structural changes in materials over multiple charge-discharge cycles. We will look at why this happens and how this heating can be reduced.
Keywords: акумулятор; smartphone